PENERAPAN MODELLING UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PUISI PADA SISWA KELAS VIIF DI SMP NEGERI 1 MOJOLABAN SUKOHARJO - Tukidi, - (Universitas Negeri Semarang, 2010)
The study was aimed at improving the ability to read a poem for year VIIF students ofState Junior High School 1 of Mojolaban Sukoharjo through modeling. The study wasan action research. The data were gathered through observation, interview, andperformance test. The reasearch was conducted in three cycles. Each cycle consistedof four stages: (1) planning, (2) action, (3) observation, (4) analysis and reflection. Itwas revealed that students ability in reading a poem improved. The performanceindicator was 50%-80% for score = 75. In cycle I, the mean score was 66.08 with12.5% passing grade. In cycle II, the mean was 74.12 with 47.5% passing grade. Incycle III, the mean was 79.25 with 77.5% passing grade.Kata kunci:modelling,membaca puisi, penelitian tindakan kelas